Hepa Water Purification Influence on Decreasing Germs Number in Isolation Treatment Room Kediri Regency Hospital - Joko Sasmito; Indasah Indasah (Syntax Corporation, 2022)
Pure and Fresh, is the air condition that everyone dreams of anywhere and anytime, including sick people in the Hospital Treatment Room. The germ index and room dust content also affect the comfort and health of residents which is a standard quality standard for microbiological and physical parameters for hospital air. This study aims to analyze the effect of HEPA air purification in reducing germ numbers in the isolation treatment room of Kediri Regency Hospital, and the specific purpose of this study is to analyze the difference in the number of airborne germs in the isolation treatment room of Kediri Regency Hospital before and after the use of HEPA air purification, This study uses a pre-experimental design. The sample of this study was 5 class 1 rooms of the Isolation Treatment Room of Kediri Regency Hospital. The sampling technique is total sampling. The Wilcokson test was used for data analysis with a significant level (Î±) = 0.05. The results of the data analysis showed that there was a difference in the number of airborne germs in the isolation treatment room of Kediri District Hospital between before the use of Air Purification HEPA and after the use of Air Purification HEPA. So the use of Air Purification HEPA has an influence on the number of airborne germs in the isolation treatment room of Kediri Regency Hospital.